PERAN PELAYANAN SEKOLAH DASAR DALAM MENDUKUNG KOTA LAYAK ANAK DI SURAKARTA - M. Dhia Subulussalam; Murtanti Jani Rahayu; Rizon Pamardhi Utomo (Universitas Sebelas Maret Surakarta, 2015)
Surakarta city is one of the first five cities that became a model in applying the concept of child friendly city. As one of the city that became the modeling of the concept of child friendly city, the city of Surakarta has made many changes to be able to realize the concept. But in Surakarta decent towards the child does not mean there are no issues. One of the problem that happens is in the field of education, especially primary schools like a gap of educational standards, filling the needs of the educational infrastructure is still not fulfilled, and the safety and comfort of children both within and outside the school. Issues contained in the education sector will have a negative impact in the process of realizing the child friendly city in Surakarta. Research question is how the role of primary education in creating child-friendly city in Surakarta. The research method is the type of deductive -quantitative research with technique analysis is descriptive quantitative and descriptive spatial by describing the spatial conditions in the field. The results of this researchis that the majority of elementary schools in Surakarta has a range of services that exceed the ideal standard, completeness infrastructure elementary school environment that is still not fullest yet and therefore have the safety and comfort on the road around the school is quite high. From the results obtained that the role of primary school services in support of child friendly city is still providing a sense of safety and comfort, although the condition of completeness lack of infrastructure facilities and elementary school services is far enough. Keywords: child friendly cities, elementary school, the role of education service